Simultaneous direct and indirect wavefront sensing using multiplexed programmable grating patterns - Pathak, B (Society of Photo-optical Instrumentation Engineers, 2021)
Direct wavefront sensing is commonly performed by using a popular Shack-Hartmann wavefront sensor. On the other hand, indirect wavefront sensing is performed based on an image quality metric by acquiring a sequence of images in which pre-determined amount of aberrations modes are incorporated. Both the sensing approaches have their advantages and disadvantages depending on specific applications. In the present work, we propose simultaneous realization of both the sensing approaches with broader applications by using a multiplexed programmable binary diffraction grating pattern. We present proof-of-concept simulation results that demonstrate the working of the proposed multiplexed grating array based wavefront sensor (MGAWS) and its flexibility in easy switching between both the sensing approaches to estimate the wavefront accurately.